Edible bird’s nest soup (EBNS) serves as anti-obesity and antilipemic after 6-weeks of supplementation in high-fat diet (HFD)-fed rats - Mohd Noor, Akmal; Abdul Razak, Intan-Shameha; Ajat, Mokrish; Abu Bakar, Md. Zuki; Mansor, Rozaihan; Ideris, Aini (Penerbit Universiti Kebangsaan Malaysia, 2024)
Traditionally, edible bird’s nest (EBN) has been trusted to have several medicinal effects in the Chinese community. One of the beneficial effects of the EBN is that it is a metabolic stimulator. This study was conducted to investigate the effect of EBN soup (EBNS) and EBN extract (EBNE) on obesity, body fat distribution, blood lipid profile, and cardiogenic indices in high-fat diet-fed rats. Obesity and dyslipidemia in rats were induced with a high-fat diet (HFD) and Triton X-100 (TX100) and supplemented with or without Simvastatin, EBNS, or EBNE for 6-weeks. Final body weight changes and body fat distribution (subcutaneous and visceral fat) were measured. Triglycerides (TAG), total cholesterol (TC), high-density lipoprotein (HDL), low-density lipoprotein (LDL), and very low-density lipoprotein (VLDL) were measured by taking blood from the lateral coccygeal vein. Subsequently, cardiogenic indices were calculated (LDL/HDL ratio (LHR) and atherogenic index (AI)). In general, the EBNS demonstrated an anti-obesity and antilipemic effect after 6 weeks of supplementation. A significant reduction in body fat deposition was also recorded in the EBNS group, including subcutaneous and visceral fat. Bad cholesterol (LDL) was significantly maintained in the normal range, and cardioprotectant cholesterol (HDL) was significantly elevated as good as Simvastatin. EBNS supplementation was also significantly predicted to reduce the risk of cardiovascular diseases and atherosclerosis development in the rat model. Nonetheless, the EBNE group was not exhibiting equivalent effects as documented in the EBNS group after 6 weeks of supplementation.